Informal consultations in infectious diseases and clinical microbiology practice - Leblebicioglu, H; Akbulut, A; Ulusoy, S; Sunbul, M; Aydin, K; Geyik, MF; Eroglu, C (Blackwell Publishing Ltd, 2003)
Informed consultation between physicians is an important part of medical practice. The aim of the study was to evaluate the nature and frequency of such consultations in infectious diseases and clinical microbiology practice. This study was done in five university hospitals. Twenty-one infectious diseases and clinical microbiology specialists participated in informal ('curbside') consultations. In a written questionnaire, physicians were asked to report the number and nature of the informal consultations (ICs) they were asked to provide. A total three hundred and sixty-two such consultations were carried out during a three-month period. The ICs occurred most frequently in the hospital (82.3%). Most of the ICs from outside the hospital were by telephone. Most of the ICs (54.4%) were requested by fellows of specialists. 78.7% of the ICs were requested during working hours. 58.8% of consultations took less than 5 min, 18.8% took 6-10 min, 15.2% took 11-20 min, and 7.2% took over 20 min. The four most common reasons for obtaining ICs were to: help to select an appropriate treatment plan (41.4%), help to select an appropriate prophylaxis (19.3%), interpret laboratory data (10.2%), and provide information about antibiotics (10.2%). 30.1% of ICs resulted in subsequent formal consultation and only four patients (1.1%) were transferred to the consultants' clinics. Informal consultations are a frequent occurrence in the practice of infectious diseases and clinical microbiology (ID&CM). Physicians use this sort of consultation to select an appropriate treatment plan and obtain medical information. This study confirms the importance of the ID&CM specialists as a resource for medical personnel.
Keywords: curbside consultation; infectious diseases and clinical microbiology; informal consultation